General procedure for determining the geometric parameters of tools in the technological systems involving machining by cutting - Botvinovska, Svitlana; Getun , Galina; Zolotova , Alla; Korbut , Ievgen; Nikolayenko, Tatyana; Parnenko , Valeriya; Rodin , Rodion (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study aiming at devising a common procedure for determining the geometric parameters of tools’ cutting part in the technological systems that involve machining by cutting. Underlying the development of this procedure is the generalized theory of determining geometric parameters on tools’ cutting blades. The analysis of determining the geometry of tool cutting edges in different coordinate systems has shown that the procedure used by a given theory depends on the type and design of tool cutting edges. In the process of cutting, the geometric parameters of tools change along the cutting edges while existing ones do not fully take into account this phenomenon. This is because geometric parameters are determined in the kinematic system of coordinates. Particularly important to meet these requirements is for the cutting process whose effectiveness depends significantly on the accuracy in selecting methods for determining tool operational parameters. In this regard, the current work has devised and proposed a general procedure for determining the geometry of tool cutting edges, directly during its application in the kinematic system. The procedure is based on the consideration of the resulting speed, in the form of the vector amount of the main movement and the amount of movement of feeds, which can consider feeds specified by the system’s equipment. This approach to the development of a general procedure ensures that the geometry of the cutting part of a tool of any design is determined along its cutting edges during operation. The devised procedure has significantly reduced the time of calculations and ensured the required geometric parameters of the cutting part of a groove cutter